2012
DOI: 10.5539/ibr.v5n10p227
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership: Lessons in Management for Today

Abstract: This paper examines the underappreciated differences between the effectiveness and measurement of current technical advances in business management methods and how aspects of transformational leadership, as exhibited by the prophet Moses, can more broadly and deeply contribute to an organization’s success over the long term than these more easily defined procedures. These leadership issues tend to arise most acutely when a company’s management comes under severe scrutiny during times of business scandals and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Servant leaders should therefore be viewed as trustees of the human capital of an organization (Berendt, 2012). Jones (2012b) investigated the effects of servant leadership on the leader-follower relationship and the resulting impact on the customer focus within the framework of employee satisfaction, empowerment, organizational culture, and performance.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Servant leaders should therefore be viewed as trustees of the human capital of an organization (Berendt, 2012). Jones (2012b) investigated the effects of servant leadership on the leader-follower relationship and the resulting impact on the customer focus within the framework of employee satisfaction, empowerment, organizational culture, and performance.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…They tend to become more sensitive to their followers, they know how to motivate them, to inspire them, and therefore, increase their performance to achieve business and organizational goals, too. Bozkurt and Goral (2014) and Mohammed et al (2012) did not find statistically significant differences between educational level and leadership style, while Berendt et al (2012) claim that today's managers need to be more educated to fulfill all business needs. Also, Barbuto et al (2007) found that the leader's level of education had a significant main effect on transactional and transformational behaviors.…”
Section: Theoretical Backgroundmentioning
confidence: 94%
“…Higher institutions are more concerned with the development of the workforces' abilities, skills, knowledge, and performance. In this connection, leaders' inspirational motivation is an important tool in nurturing employees' competencies, skills, and performance (Berendt, Christofi, Kasibhatla & Maruffi, 2012). Inspired employees, through their potential and efforts, can apprehend desired standards only when they have persistent support from their leaders.…”
Section: Introductionmentioning
confidence: 99%